The contribution of bank regulation and fair value accounting to procyclical leverage - Amel-Zadeh, Amir; Barth, Mary E.; Landsman, Wayne R. (Review of Accounting Studies, 2017)
Our analysis of how banks’ responses to asset price changes can result in procyclical leverage reveals that, for banks with a binding regulatory leverage constraint, absent differences in regulatory risk weights across assets, procyclical leverage does not occur. For banks without a binding constraint, fair value and bank regulation both can contribute to procyclical leverage. Empirical findings based on a large sample of U.S. commercial banks reveal that bank regulation explains procyclical leverage for banks relatively close to the regulatory leverage constraint and contributes to procyclical leverage for those that are not. We also show that fair value accounting does not contribute to procyclical leverage.